𝒩-Fuzzy Ideals in Ordered Semigroups. (3rd November 2009) - Khan, Asghar; Jun, Young Bae; Shabir, Muhammad
Abstract : We introduce the concept of𝒩 -fuzzy left (right) ideals in ordered semigroups and characterize ordered semigroups in terms of𝒩 -fuzzy left (right) ideals. We characterize left regular (right regular) and left simple (right simple) ordered semigroups in terms of𝒩 -fuzzy left (𝒩 -fuzzy right) ideals. The semilattice of left (right) simple semigroups in terms of𝒩 -fuzzy left (right) ideals is discussed.